2017
DOI: 10.1016/j.juro.2017.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Changes in Brain Activity during Sacral Neuromodulation for Overactive Bladder

Abstract: Functional magnetic resonance imaging confirmed that sacral neuromodulation influences brain activity in women with overactive bladder who responded to therapy. These changes varied with stimulus intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 24 publications
3
42
1
2
Order By: Relevance
“…It has been postulated that the clinically observed contraction of the PFM upon stimulation of the sacral spinal nerves, represented by the bellows response, is correlated to reflex responses (R2 and R3 EPFMR) mediated by afferent input to the spinal cord 5,6 . This observation has served as one of the key findings in the generation or confirmation of hypotheses on the mechanism of action of SNM 7‐9 …”
Section: Introductionmentioning
confidence: 98%
“…It has been postulated that the clinically observed contraction of the PFM upon stimulation of the sacral spinal nerves, represented by the bellows response, is correlated to reflex responses (R2 and R3 EPFMR) mediated by afferent input to the spinal cord 5,6 . This observation has served as one of the key findings in the generation or confirmation of hypotheses on the mechanism of action of SNM 7‐9 …”
Section: Introductionmentioning
confidence: 98%
“…The authors reported activation of the right inferior frontal gyrus independent of stimulation amplitude. Increasing the stimulation amplitude activated several brain areas, whereas subsensory stimulation was noted to only reduce activity in the pons and periaqueductal grey matter [34]. These two studies indicate that SNS influences brain activity, that neuromodulation takes place and that the stimulation intensity has an effect on the amount of neuromodulation.…”
Section: Discussionmentioning
confidence: 78%
“…The mechanisms underlying the effectiveness of neuromodulation strategies to control bladder function are not fully understood. Recent thinking is that activation of afferents by low‐frequency stimulation results in a change in bladder perception threshold and an increased bladder capacity, almost certainly mediated via a central mechanism . The effectiveness of high‐frequency stimulation is also thought to be due to activation of afferent fibers, albeit likely via engagement of a different central mechanism .…”
Section: Discussionmentioning
confidence: 99%